Modulating Oxygen Affinity to Enhance Liquid Products for the Electrochemical Reduction of Carbon Monoxide - Jiayi Chen; Juan Manuel Arce‐Ramos; Ioannis Katsounaros; Emiel deSmit; Saifudin M. Abubakar; Yanwei Lum; Jia Zhang; Lei Wang (SmartMat)
ABSTRACT Electrocatalytic CO reduction (COR) offers a promising alternative approach for synthesizing valuable chemicals, potentially at a lower carbon intensity as compared to conventional chemical production. Cu‐based catalysts have shown encouraging selectivity and activity toward multi‐carbon (C2+) products, albeit typically in the form of a mixture. Steering COR selectivity toward specific types of C2+ products, such as liquid products with high energy density, remains a challenge. In this study, we developed a Cu/Zn bimetallic catalyst composite and demonstrated enhanced selectivity toward liquid products as compared to reference CuO and Cu‐based catalysts, approaching 60% at a high current density of 300 mA/cm2. Our investigation highlights that the introduction of Zn promoted the emergence of a Cu/Zn heterojunction interface during COR. Density functional theory simulations were used to rationalize the observed differences in selectivity, revealing that interface plays a crucial role in diminishing the oxygen adsorption at the Cu‐sites and modifying the adsorption energy of COR reaction intermediates, consequently leading to enhanced selectivity toward liquid products.